Sierra Leone : Ex Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report, 2005)
This paper presents an Ex Post Assessment of Longer-Term Program Engagement for Sierra Leone. Sierra Leone has had almost continuous involvement with IMF programs since 1994 under a variety of arrangements. All the IMF-supported programs in Sierra Leone during 1994-2004 had the same overarching aim of raising long-term growth and reducing poverty. Their near-term objectives, however, varied with existing circumstances. Each of the programs emphasized disciplined macroeconomic policies and structural reforms. Performance relative to program objectives improved over time and was the strongest under the Poverty Reduction and Growth Facility.